Relações de consumo no mundo contemporâneo: função social do estado na efetivação da proteção dos consumidores - Oliveira, Fábio Dias de (2024)
This research aims to deepen the understanding of consumer relations and their interconnection with the State, which is considered responsible for consumer protection, when exercising, in the contemporary world, this true social function. To this end, this work briefly addresses the historical evolution of consumer relations and their interaction with the State, referring to the creation of legal standards to guarantee consumer protection, which challenge the effectiveness of the exercise of the social function of the State in the face of these relations. It goes through foreign legislation protecting consumer relations, seeking to understand some main differences between them and Brazilian legal standards for consumer protection, always focusing on the exercise of the State's social function in view of the effectiveness of this protection. It inserts consumer relations in the environment of the new industrial revolution, bringing important current concepts and considerations about electronic commerce (ecommerce), and references on attempts to standardize consumer relations on the internet, such as the norms contained in the General Law of Data Protection and the Internet Civil Framework. Finally, the studies refer to some situations of (in)enforcement of rights in consumer relations, during the Covid-19 pandemic, seeking to relate themes that, apparently, are heterogeneous, but which, nevertheless, involve “intertwined threads, in a same plot"